ANALISIS KEMAMPUAN BERPIKIR KREATIF MAHASISWA KELOMPOK ATAS DALAM MENYELESAIKAN SOAL STRUKTUR ALJABAR RING MATERI IDEAL PRIMA DAN IDEAL MAKSIMAL - Inayah Rizki Khaesarani Nayah; Siti Maysarah (Program Studi Pendidikan Matematika, 2021)
This study aims to describe the creative thinking ability of upper group students in solving Ring Algebra Structure questions on the prime ideal and maximum ideal material. This research uses descriptive qualitative research. The research subjects are students of Mathematics Education-2 Semester VI who have taken the Ring Algebra Structure course. The research subjects are three (3) students of Mathematics Education-2 Semester VI who have high mathematical abilities based on test results in the form of assignments on Ideal material. The instruments used in the study include: 1) Test; 2) Interview guide; and 3) Documentation. Based on the results of research and discussion, the findings resulted that the thinking ability of upper-class students had fulfilled all aspects of creative thinking, namely fluency, flexibility, and originality. The subject has been able to explain all the indicators that have been set very well and precisely. Subjects have also been able to prove prime ideals or maximum ideals or not both and can identify examples and non-examples of prime ideals and maximum ideals through high-level elaboration and analysis carried out by the subject. Subjects are also very able to describe Lattice diagrams on each question and can determine the subring of a ring. It's just that there is a uniqueness of the worksheet between MS, ZB, and HF. But overall the subject has fulfilled the creative thinking aspect. Thus, it can be concluded that the upper group students can be categorized at level 4, which is very creative.